Enzymatic properties and biological activity of resuscitation-promoting factor B of Rhodococcus sp. (GX12401) - Gong, Xu; Lu, Huijiao; Wu, Jiafa; Zhou, Yan; Yang, Lifang; Wang, Yibing; Shen, Naikun; Jiang, Mingguo (Frontiers in Microbiology, 2022)
Resuscitation promoting factor B (RpfB) is one of the five members of Rpf-like family in mycobacteriales, which have the resuscitation-promoting activity. Most strains of Rhodococcus also have RpfB gene, but the study of rpfB gene in Rhodococcus is not thorough. Here, we amplified the rpfB gene of intact Rhodococcus sp (GX12401) and cloned it into pET30a (+) expression vector. Then a recombinant form of soluble RpfB was expressed in Escherichia coli BL21. The soluble recombinant RpfB was purified by Ni–Sepharose affinity chromatography and molecular weight of the protein was 55 kDa, determined by 12% SDS–PAGE stained with Coomassie brilliant blue R-250. When 4-methylumbelliferyl-β-D-N,N',N''-triacetylchitoside was used as enzyme substrate to test lysozyme activity, the recombinant protein RpfB had good stability and enzyme activity, and the lysozyme activity was low (4.74U), among which Mg2+, Na+, Al3+ and DMSO could significantly increase the activity of RpfB. The purified recombinant protein was added to Rhodococcus VBNC cells, and the VBNC cells were resuscitated at the concentration of 1 picomolar concentrations, which increased by 18% compared with the control, while the cell resuscitation was inhibited at the concentration of 1000 picomolar concentrations. Therefore, RpfB can improve the survival ability of Rhodococcus in extreme or harsh environment and enhance the corresponding biological activity.